Effects of Qutan Huoxue Formula on the SOCS1/TLR4 Signaling Pathway in NASH Model Mice. (21st November 2020) - Zhang, Yurong; Zhu, Xiaoning; Zheng, Ding; Yin, Yue; Peng, Mengyun; Wang, Jing
Abstract : The purpose of this study was to investigate the effects of Qutan Huoxue Formula (QHF) on liver injury in mice with nonalcoholic steatohepatitis (NASH) by upregulating SOCS1 to inhibit the TLR4/NF- κ B signaling pathway. Thirty male C57BL/6J mice (20–22 g) were randomly divided into the normal diet group (ND group), methionine- and choline-deficient diet group (MCD group), and Qutan Huoxue Formula group (QHF group). Mice in the ND group were fed a regular diet, while mice in other two groups were fed MCD diet. After successful molding, the QHF group was gavaged by QHF. The ND group and MCD group were gavaged by the same volume of normal saline, once a day. During the period of gavaging, all mice continue to be fed MCD fodder except for the ND group. All mice were killed at 8 w. H&E staining and Oil Red O staining were used to observe the pathological changes of liver tissues. Serum level of ALT, AST, TC, and TG was detected by enzyme-linked immunosorbent assay. The expression of liver SOCS1, TLR4, Myd88, and NF- κ B was detected by real-time PCR, immunohistochemistry, and Western blot. QHF can significantly reduce the serum levels of ALT, AST, TC, and TG of NASH mice and reduce the degree of liver fat degeneration and inflammation. It also can decrease both mRNA and protein expressions of liver TLR4, Myd88, and NF- κ B. The mRNA expression of SOCS1 increased, while the SOCS1 protein expression decreased. In conclusion, QHF can significantly alleviate hepatic steatosis and inflammation in NASH mice by upregulating SOCS1 to inhibit the TLR4/NF- κ B signaling pathway.